STRATEGI PENGEMBANGAN WINE TOURISM DI KABUPATEN BULELENG-BALI - Gita Dewi Ayu, Putu; Kusuma Negara, I Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 1 (2018): Jurnal IPTA (July 2018)DO - 10.24843/IPTA.2018.v06.i01.p01, 2018)
Every tourism potential owned by Bali needs to be studied, researched and developed in order to meet the needs of the economy community. One of the tourism potential that needs to be developed in Bali is the wine tourism. Buleleng Regency is one of the largest wineries and also the house of the oldest wine factory on the island of Bali. But there are still many foreign tourists who are not aware of the existence of the wine producing region. This study aims to determine the perception of tourists about the wine products and to know the development strategy that must be done in order to support the activities of wine tourism in Buleleng Regency. The results of this study showing that the tourists perception regarding Bali wine product shows that they feel the quality of the products is good and also shows their interest to do wine tourism in Buleleng Regency. Based on the results of SWOT analysis, there are several strategies that can be applied to develop the wine tourism such as increasing the promotion of tourism in Bali to be better known by foreign tourists, government working together with the wine-producing companies to jointly develop wine tourism activities in Buleleng, and the last by expanding the area of wineries in the district of Buleleng so there is an image or existence of wine tourism in Buleleng. In connection with the results and discussion in this study, the suggestion that is expected to be done by the government is to work with companies that produce wine in improving the quality of products and services, and pay attention to periodicity and innovation on a regular basis.